Effect of ilioinguinal/iliohypogastric nerve block with dexmedetomidine/ropivacaine on quality of life for elective open unilateral inguinal hernia repair in adults: a Mexican multicentric, randomized controlled trial study - Castillo Martínez, Daniel Benito (International Journal of Research in Medical Sciences, 2023)
Background: Hernia surgery is one of the most frequent procedures performed worldwide, with a prevalence of postoperative groin pain above 30%. Quality of life in hernia surgery has been poorly studied. Objective was to determine the effect on the quality of life of dexmedetomidine as a local anesthetic adjuvant in elective unilateral open inguinal repair. Methods: A multicenter, prospective, randomized, single-blind, cases and controls study was carried out that included 46 male patients between 18 and 85 years scheduled to undergo elective unilateral open inguinal repair at the north central PEMEX Hospital between November 2021 and November 2022. Sample was divided in two groups, Group A for ilioinguinal and iliohypogastric nerve block with dexmedetomidine/ropivacaine and Group B ropivacaine alone, SF-36 was measured in preoperative consult and a second measure 90 days after surgery, differences between first and second measure were analyzed, and statistical analysis was performed with the statistical software IBM® SPSS© statistics. Results: Significant difference in pre-test/post-test shifts between groups in physical functioning (PF), role limitation due to physical health (RLPH), emotional well-being (EW-B), and health change (HC) in favor of group A. Conclusions: The ilioinguinal and iliohypogastric nerve block with dexmedetomidine/ropivacaine improves life quality in hernia surgery patients.